Vertical tax competition in Brazil: Empirical evidence for ICMS and IPI in the period 1995-2009 - Rodolfo Herald da Costa Campos; Roberto Tatiwa Ferreira; Rafael Kloeckner (EconomiA, 2015)
The main objective of this study is to quantify the impact caused by changes in federal tax on the tax policy of the Brazilian states, considering the presence of horizontal tax competition between states. Using panel data covering 26 Brazilian states plus the Federal District during the period 1995–2009, two models were estimated representing the average reaction of the states in response to changes in federal tax rates. In the first model, both levels of government act simultaneously, whereas in the second model, reaction is sequential, with the federal government acting as the leader in defining its effective tax rates. The results indicate a positive and significant response of states to increases in the federal tax rate, resulting in an over-taxation of the common tax base and higher tax rates. Additional tests show that the first model is the most suitable to represent the problem analysed. – – Objetivo principal desse trabalho é quantificar qual o impacto provocado por mudanças no imposto federal sobre a política tributária dos estados, considerando a presença de competiç\~ao tributária horizontal entre os estados. Utilizando um painel de dados que abrange os 26 estados brasileiros mais o Distrito Federal no período 1995–2009, foram estimados dois modelos que representam a reaç\~ao média dos estados em resposta a mudanças nas alíquotas do governo federal. No primeiro modelo ambos os níveis de governo agem simultaneamente, enquanto que no segundo a reaç\~ao é sequencial com o governo federal atuando como líder na definiç\~ao de suas alíquotas efetivas. Os resultados apontam para uma resposta positiva e significante dos estados à aumentos na alíquota tributária federal resultando em uma sobretaxaç\~ao da base tributária comum e alíquotas elevadas. Testes adicionais mostram que o primeiro modelo é o mais indicado para representar o problema analisado.
Keywords: E62; H20; H77; 330; Fiscal federalism; Tax competition; Horizontal and vertical tax externalities; Reaction functions